Pemasaran Digital Terintegrasi Terhadap Loyalitas Pelanggan - Asrizal Efendy Nasution; Linzzy Pratami Putri; Rini Astuti Astuti (JURNAL ILMIAH MANAJEMEN & BISNIS, 2022)
Purpose - This study aims to determine the right promotion concept for 212 Mart Medan with variables studied are sales promotion, advertising, direct marketing and public relations in increasing customer loyalty.Methodology - Data collection is done through a questionnaire with a sampling technique used random sampling by using 100 customers of 212 Mart Medan. Data processing using Structural Equation Model (SEM) analysis.Findings - The results of this study indicate that the variables of sales promotion, advertising, direct marketing and public relations have a significant influence on customer loyalty at 212 Mart Medan.Originality/Novelty - Digital marketing model through the Website, Facebook (FB), Instagram IG), and Whatsapp Group (WAG) which are integrated with social media owned by FOSIL BKM MEDAN as a forum for gathering representatives of mosque management to mobilize Muslims united to build sharia economy through shopping at 212 Mart Medan.Implications - With the availability of those media, 212 Mart Medan can be used as a place for sales promotion, advertising, direct marketing, public relations in an effort to increase customer loyalty